Ecotourism: A practical guide of Megapodius reinwardt for prospective teacher - Muhammad Yamin; A. Wahab Jufri; Alifman Hakim; Gunawan Gunawan; AA Sukarso (Jurnal Pijar Mipa, 2023)
Learning activities can be carried out in or outside the classroom. Learning outside the classroom, such as field observations, is an excellent learning activity. This paper discusses the development of a field observation practicum guide for bird bioecology Megapodius reinwardt. The goal is to develop and assess the feasibility of the developed practical guide, the process of scientific literacy, and the critical thinking skills of prospective biology teacher students through three stages: define, design, and develop. Data collection through observation, interviews, questionnaires, tests, and documentation. The data obtained were analyzed by descriptive quantitative. An average of 77% obtained the results of the practical guide validation, which means worthy. The process of scientific literacy of prospective biology teacher students, on average, obtains a good predicate. User response is positive, so it is suitable for use as a bioecological Field Observation Guide Megapodius reinwardt for the literacy process scientific and thinks student critical biology teacher candidate.